Making the Chinese Mexican : global migration, localism, and exclusion in the U.S.-Mexico borderlands. - Delgado, Grace (Stanford University Press, 2012)
Making the Chinese Mexican is the first book to examine the Chinese diaspora in the U.S.-Mexico borderlands. It presents a fresh perspective on immigration, nationalism, and racism through the experiences of Chinese migrants in the region during the late nineteenth and early twentieth centuries. Navigating the interlocking global and local systems of migration that underlay Chinese borderlands communities, the author situates the often-paradoxical existence of these communities within the turbulence of exclusionary nationalisms. The world of Chinese fronterizos (borderlanders) was shaped by th.